Pemeriksaan Escherichia coli, Staphylococcus aureus dan Salmonella sp. pada Jamu Gendong yang Dijajakan di Kota Medan - Sri Fhitryani; Dwi Suryanto; Abdul Karim (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
This study aims to determine the presence of the bacterium Escherichia coli, Staphylococcus aureus and Salmonella sp. in carrying medicinal sold on the five areas in the city of Medan. This study was conducted descriptive of the results of bacterial contamination in carrying medicinal by the number of 20 samples of 5 herbalist carrying in different areas in the city of Medan. The sampling sites are the Menteng area, with a total population carrying medicinal sellers there are 5 people, Literacy area 5, area Tembung 4 people, Sunggal area 3 and area Sei Sekambing 3. Test results Staphylococcus aureus and Salmonella sp. at 5 locations showed negative results and the results of the Total Plate Count 102 at location A (Menteng), namely 3, location B (Traditional), namely 5, the location is C (Tembung) ie 4, the location of D (Sunggal) ie 8 and Area E (Sei Sikambing) is 5. the confirmation test results using BGLB media to determine the negative results (no gas formation) and media testing with Mac-Conkey to grow colonies of pink. On the positive Sunggal local herbal samples contaminated with bacteria coli and other microbial species are not found. This contamination as a result of the manufacturing process that is less attention to elements of sanitation and hygiene as well as the contamination of air at the time of sale and packaging.